Interannual variability in hydrography and water mass distribution in Hornsund, an Arctic fjord in Svalbard. Issue 1 (1st January 2018) - Promińska, Agnieszka; Falck, Eva; Walczowski, Waldemar
ABSTRACT: Progressing warming in the Arctic and increased extreme weather events can significantly influence the hydrography of Svalbard fjords, leading to changes towards more Atlantic-type waters in the fjords. In this paper, we look into the hydrographic conditions in Hornsund, the southernmost fjord on the west coast of Svalbard, by analysing high-resolution CTD measurements collected in July during cruises with the RV Oceania between 2001 and 2015. These observations revealed high interannual variability in temperature, salinity and distribution of water masses, mainly due to differences in timing of the transition between winter and summer conditions but also as a result of changing environmental factors such as air temperature and sea-ice cover. Hornsund shows weak Atlantic Water occupation, probably due to strong influence of the Sørkapp Current along the southern coast of Spitsbergen. The main basin of the fjord was much more influenced by waters entering the fjord from outside than the inner basin, Brepollen, which was mainly characterized by the presence of locally formed Winter Cooled Water (WCW). The amount and properties of WCW in Brepollen revealed high variability after 2006, and no WCW in July 2012. The results of our study show that Hornsund is highly variable and susceptible to recently observed atmospheric and oceanic extreme events in the Svalbard region.